Differences in Food Security Based on Family Income and Its Impact on Stunting Among Children Under Five in Padang Lawas Regency North Sumatera Province - Sri Melda Br Bangun; Nur Indrawati Lipoeto; Novizar Nazir; Rosfita Rasyid; Yonariza Yonariza; Hardisman Hardisman; Masrul Masrul; Firdawati Firdawati (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Indonesia continues to face nutritional challenges, with a high prevalence of stunting. incidence Padang Lawas Regency is one of the regions in North Sumatra Province with a relatively high of stunting. Stunting is influenced by several factors, one of which is food security. Food security depends on family income; inadequate family income leads to poor food security, making families unable to meet children's primary and secondary needs. This study aims to analyze differences in food security based on family income and its impact on stunting incidence among children under five in Padang Lawas Regency North Sumatera Province. This research is an analytical survey using a cross-sectional study design. The study was conducted in Padang Lawas Regency, specifically in six sub-districts with the highest number of children under five: Sosa, Hutaraja Tinggi, Barumun, South Barumun, Batang Lubu Sutam, and Sosa Julu. The research was carried out from October 2024 to February 2025. The study population consisted of all families with children aged 6-59 months across the six sub-districts, totaling 9,181 families. Using Slovin's formula, the sample size was determined to be 384 families. A multistage cluster sampling technique was employed for sample selection. Data collection was conducted through interviews and observations. Data analysis included univariate analysis and bivariate analysis using an independent t-test and simple logistic regression with a significance level of 95% (α = 0.05). The study results indicate a significant difference in food security based on family income (P-value = 0.001). Moreover, there is a significant impact of family food security on stunting incidence among children under five in Padang Lawas Regency (P-value = 0.001; Exp.B = 13.908). It is recommended that the Padang Lawas Regency Government improve the local economic system by facilitating job opportunities for the community. Keywords: Family income, food security, stunting